AKTIVITAS ANTIBAKTERI EKSTRAK DAUN Cyclea barbata (L.)Miers. TERHADAP BAKTERI Escherichia coli DAN Salmonella typhi - Arifan Asmardi; Rodesia Mustika Roza; Fitmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Indonesia has many medicinal plant species that are distributed in many regions. Green grass jelly (Cyclea barbata (L.) Miers.)is one of medicinal plant that used in traditional medicine by Indonesian people. This species used to treat inflammation, fever and others. The main content of green grass jelly are saponins, flavonoids and alkaloids. Escherichia coli and Salmonella typhi can infect the human body, but the green grass jelly can inhibit the growth of these bacteria. This study was performed using four methods, maceration, fresh leaf grinding, fresh and dried leave boiling, the dilution series (10%, 25%, 50%, 75% and 100%) were applied for each method. The best result among four methods was the maceration method with 100% concentration dilution. The treatment using E. coli showed the widest diameter of inhibition zone was 17.23 mm and the lowest diameter was 7,70 mm. while the treatment using S. typhi showed the widest diameter was 15.89 mm and the lowest diameter was 6,85 mm. The higher the concentrations used, the wider the inhibition zone diameter was.